Never Alone. A study of Articulations of Indigenous Religion in the Video Game - Lohne, Inger Lise Damli (UiT Norges arktiske universitet, 2020)
This thesis explores the many ways indigenous religion is articulated, performed and translated in the video game Never Alone - Kisima Inŋitchuŋa (2014). The video game was among the first of its kind – being made in a close collaboration with an indigenous group, and published by the first indigenous owned video game company in the U.S.A. At launch, Never Alone gathered attention from traditional media in both North America and in Europe, and the game reached a global audience. Never Alone tells a story based on Inupiat storytelling, and Cultural Ambassadors gives the player an insight into Inupiat culture and tradition. Never Alone balances on the edge between the conventions of the video game medium and its genres, and of indigenous tradition and religion. This thesis examines how vocabularies that can be related to ‘indigenous religion’ are used and translated in Never Alone, and how these vocabularies relate to a globalizing discourse on indigenous religion. This thesis also explores how the medium of video games facilitates new ways of reclaiming traditions and articulating indigenous religion.
Keywords: 1-Jeux vidéo; 2-Épistémologies autochtones; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Europe (lieu de production du savoir); 5-Créateur.rice autochtone; _Nettoyé

Control mapping: Peter Pitseolak and Zacharias Kunuk on reclaiming Inuit photographic images and imaging - Winfield, Norman David (Decolonization: Indigeneity, Education & Society, 2014)
Inuit have been participating in the development of photo-reproductive media since at least the 19th century, and indeed much earlier if we continue on Michelle Raheja’s suggestion that there is much more behind Nanook’s smile than Robert Flaherty would have us believe. This paper examines how photographer Peter Pitseolak (1902-1973) and filmmaker Zacharias Kunuk have employed photography and film in relation to Raheja’s notion of “visual sovereignty” as a process of infiltrating media of representational control, altering their principles to visualize Indigenous ownership of their images. For camera-based media, this pertains as much to conceptions of time, continuity and “presence,” as to the broader dynamics of creative retellings. This paper will attempt to address such media-ontological shifts – in Pitseolak’s altered position as photographer and the effect this had on his images and the “presence” of his subjects, and in Kunuk’s staging of oral histories and, through the nature of film as an experience of “cinematic time,” composing time in a way that speaks to Inuit worldviews and life patterns – as radical renegotiations of the mediating properties of photography and film. In that they displace the Western camera’s hegemonic framing and time-based structures, repositioning Inuit “presence” and relations to land within the fundamental conditions of photo-reproduction, this paper will address these works from a position of decolonial media aesthetics, considering the effects of their works as opening up not only for more holistic, community-grounded representation models, but for expanding these relations to land and time directly into the expanded sensory field of media technologies.
Keywords: 1-Cinéma; 1-Histoire de l'art; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Europe (lieu de production du savoir); 5-Créateur.rice autochtone; _Nettoyé